An empirical growth model for major oil exporters - Hadi Salehi Esfahani; Kamiar Mohaddes; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper develops a long-run growth model for a major oil exporting economy and derives conditions under which oil revenues are likely to have a lasting impact. This approach contrasts with the standard literature on the 'Dutch disease' and the 'resource curse', which primarily focuses on short-run implications of a temporary resource discovery. Under certain regularity conditions and assuming a Cobb-Douglas production function, it is shown that (log) oil exports enter the long-run output equation with a coefficient equal to the share of capital (a). The long-run theory is tested using quarterly data on nine major oil economies, six of which are current members of OPEC (Iran, Kuwait, Libya, Nigeria, Saudi Arabia, and Venezuela), plus Indonesia which is a former member, and Mexico and Norway, which are members of the OECD. Overall, the test results support the long-run theory. The existence of long-run relations between real output, foreign output and real oil income is established for six of the nine economies considered. The exceptions, Mexico and Norway, do not possess sufficient oil reserves for oil income to have lasting impacts on their economies. At their current production rates, the proven oil reserves of Mexico and Norway are expected to last 9 and 10 years respectively, as compared to reserve-production ratios of OPEC members, which lie in the range of 45 to 125 years. For Indonesia, whose share of oil income in GDP has been declining steadily over the past three decades, the theory suggests that the effect of oil income on the economy's steady state growth rate will vanish eventually, and this is indeed confirmed by the results. Sensible estimates of á are also obtained across the six economies with long-run output equations, and impulse responses are provided for the effects of shocks to oil income and foreign output in these economies.
Keywords: C32; C53; E17; F43; F47; Q32; 330; growth models; long run and error correcting relations; major oil exporters; OPEC member countries; oil exports and foreign output shocks